2018
DOI: 10.30831/akukeg.380762
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye ve Almanya-Hamburg Hayat Bilgisi Dersinin Karşılaştırılması: Genel Bir Bakış

Abstract: The purpose of this study is to compare the current curricula of the life science courses implemented in Turkey and Germany-Hamburg to reveal the similarities and differences between them. Germany-Hamburg was chosen for comparison because the life science course, which is called social sciences course in many countries, taught there has a similar structure to the one taught in Turkey. The common aspects of these two countries make the conclusion more meaningful. Literature review was conducted first to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…As a result, the assessment element hinders the way to a complete alignment. Overall, it can be said that assessment element in life sciences should not be used as an element to create pressure on students (Baysal, Tezcan, & Arac, 2018). However, this does not mean that assessments to be made may lack the ability to measure objectives.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…As a result, the assessment element hinders the way to a complete alignment. Overall, it can be said that assessment element in life sciences should not be used as an element to create pressure on students (Baysal, Tezcan, & Arac, 2018). However, this does not mean that assessments to be made may lack the ability to measure objectives.…”
Section: Discussion Results and Suggestionsmentioning
confidence: 99%
“…In addition, Life Studies can be seen as important in terms of being the basis of Social Sciences and Science course. Life Studies course constitutes the basis of Science and Social Studies course (Baysal, Tezcan and Araç, 2018). As a result, the student may be inadequate in future classes due to a lack of learning in the previous classes.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Ek olarak Hayat Bilgisi, Sosyal Bilimler ile Fen Bilimleri dersine temel teşkil etmesi açısından da önemli görülebilmektedir. Hayat Bilgisi dersi Fen ve Sosyal bilimler dersine temel oluşturmaktadır (Baysal, Tezcan ve Araç, 2018). Böyle olunca önceki sınıflarda oluşabilecek bir öğrenme eksikliği nedeniyle öğrenci ileriki sınıflarda hazırbulunuşluk açısından yetersiz kalabilmektedir.…”
Section: Introductionunclassified
“…In the literature, it has been determined that there are studies comparing the Life Science Curriculum between Türkiye and Germany (Baysal et al, 2018;Canbulat, 2018;Tekgöz, 2017), studies comparing the technological competencies of the curricula (Keskin, 2017), and studies comparing the Life Science Curriculum in Türkiye with the Russian "The World Around Us" Curriculum (Ütkür Güllühan & Guseinova, 2021). However, no research comparing the Life Science Curriculum in Türkiye and Azerbaijan has been found.…”
Section: Introductionmentioning
confidence: 99%